2020
DOI: 10.3390/microorganisms8101492
|View full text |Cite
|
Sign up to set email alerts
|

Renin Angiotensin System, COVID-19 and Male Fertility: Any Risk for Conceiving?

Abstract: The current knowledge concerning the connection between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the renin–angiotensin system (RAS) system in the male reproductive apparatus is still limited, so dedicated studies are urgently required. Concerns about the male fertility consequences of SARS-CoV-2 infection have started to emerge, since epidemiologic studies observed that this coronavirus affects male patients more frequently and with increased severity, possibly because of the hormone-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 166 publications
0
35
0
2
Order By: Relevance
“…Brodin has discussed the immune-system differences between old and young people and men and women and other associated immunological factors towards the disease presentations and severity [172]. As per the previous studies, a disturbance in fertility in male patients is also expected due to the hormone-regulated expression of the ACE2 receptor [173]. However, the relationship between SARS-CoV-2 and renin-angiotensin system (RAS) in male reproductive apparatus is still unclear.…”
Section: Degree Of Difference In Cytokines Storm In Relation To Age Sex and Co-morbiditiesmentioning
confidence: 96%
“…Brodin has discussed the immune-system differences between old and young people and men and women and other associated immunological factors towards the disease presentations and severity [172]. As per the previous studies, a disturbance in fertility in male patients is also expected due to the hormone-regulated expression of the ACE2 receptor [173]. However, the relationship between SARS-CoV-2 and renin-angiotensin system (RAS) in male reproductive apparatus is still unclear.…”
Section: Degree Of Difference In Cytokines Storm In Relation To Age Sex and Co-morbiditiesmentioning
confidence: 96%
“…All available studies indicate that COVID-19 could influence male reproductive health and it is suggested that the effect of SARS-CoV-2 in the male reproductive system should be considered [ 13 ]. Accordingly, this study was designed to elucidate the impacts of SARS-CoV-2 on the male reproductive system by investigating damage of BTB and histological change in human testis.…”
Section: Introductionmentioning
confidence: 99%
“…Coronaviruses are a family of positive-sense singlestranded RNA viruses that cause infections in birds and mammals as well as humans, inducing respiratory, hepatic, neurological and gastrointestinal diseases [1]. The novel coronavirus SARS-CoV-2 causes pneumonia, a severe acute respiratory disease .…”
Section: Introductionmentioning
confidence: 99%